Intelligent contracting: Software agents, corporate bodies and virtual organizations - Andrade, Francisco Carneiro Pacheco (2007)
Legal doctrine starts to speak out of Inter-systemic electronic contracting. In this form of contracting, an important role is played by intelligent software agents, which may be fictioned as tools controlled by humans or faced as subjects of electronic commerce; may be seen as legal objects or as legal subjects. The use of software agents in electronic commerce scenarios must be connected with the existence of corporate bodies and Virtual Organisations. The issue to be discussed here is whether there should be Commercial Corporations for the use of Software Agents (as mere tools of the companies) or if the agents themselves can be seen as full and active participants in new types of commercial corporations and Virtual Organisations.